Scientific knowledge as technical knowledge: MIT's economics department and the translation of fundamental research into applications - Camila Orozco Espinel (Duke University, Center for the History of Political Economy (CHOPE), 2019)
The economics Department at the Massachusetts Institute of Technology provides a field well befitting to study the translation in the discipline of economics of "esoteric research" into "tools". Certainty, MIT was not the only bridge in economics connecting the academic and the practical arenas. Nevertheless, at MIT the connection was accomplish throughout a particular conception of science as a technical form of knowledge. Concretely, at MIT the translation was operationalized through the use of mathematical, yet simple, models that aimed first to understand a few aspects of a situation, and then to be applied to a wide range of issues. Although Samuelson's and Solow's approaches to modeling were different, their work put forward the guidelines and incarnates MIT's way of translating "esoteric research" into "tools". This paper analyses how in the context of an engineering school closed related to the war and postwar political and military powers, MIT economists advanced the frontier of the discipline into the practical arena.
Keywords: 330; MIT